2020
DOI: 10.3390/agronomy10060764
|View full text |Cite
|
Sign up to set email alerts
|

Management Drives Differences in Nutrient Dynamics in Conventional and Organic Four-Year Crop Rotation Systems

Abstract: Application of exogenous N fertilizers provides agronomic benefits but carries environmental liabilities. Managing benefits and liabilities of N-based fertilizers in conventional (CNV) and organic (ORG) cropping systems might be improved with better knowledge of nutrient dynamics, the generation of intrinsic N, and maintenance of soil organic matter. This study evaluated mineral N dynamics, yields, residue inputs, and change in soil organic C (SOC) and total N (TN) in strip-tilled, four-year crop rotations [co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…The addition of plant residues from green manure and their incorporation into soil activates the subsequent physico-chemical protection of organic carbon [ 48 ]. Prolonged application of no-tillage and the accumulation of organic matter of different availability in the soil increases the soil’s capacity to supply available nitrogen by generating intrinsic resources [ 49 ]. This contributes to an improvement in plant nutrition with nitrogen in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of plant residues from green manure and their incorporation into soil activates the subsequent physico-chemical protection of organic carbon [ 48 ]. Prolonged application of no-tillage and the accumulation of organic matter of different availability in the soil increases the soil’s capacity to supply available nitrogen by generating intrinsic resources [ 49 ]. This contributes to an improvement in plant nutrition with nitrogen in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…Kebrom et al [26] identified phytotoxic levels of copper and nickel in commercial organic soil amendments recycled from poultry farms and municipal wastes and found that commercial chicken manure and Milorganite (recycled from municipal waste) were more phytotoxic than poultry manure. Application of exogenous N fertilizers (poultry or chicken manure and/or biosolids such as Milorganite) provides agronomic benefits but carries environmental liabilities [30]. For example, higher cumulative CO 2 emissions for the soils amended with chicken manure and Milorganite but the lowest for the soils amended with dairy manure were reported by Ray et al [31].…”
Section: Introductionmentioning
confidence: 97%